Tecnologia de aplicação de fungicidas no patossistema Triticum aestivum - Puccinia triticina - Canova, Eduardo (2015)
The wheat cultivation is subject to a certain number of limiting factors, such as climate adversities and diseases. Besides contributing to the incidence of infections that arise from diseases such as leaf rust (Puccinia triticina), climatic factors affect the applications behavior of foliar fungicide. This work aimed to evaluate the applications of fungicide carried out at different times using different rates and spectra of drops in wheat plants. A field experiment was then conducted in Itaara/RS. The experiment was arranged in random blocks with sub-split parcels in factorial arrangement of 5x3x2, with four replications. The first factor was composed by the time of application (05:00, 09:00, 13:00, 17:00, 21:00). The second factor consisted of the application rates (70, 100, 140 L/ha), and lastly, two drops spectra (fine and medium) composed the third factor. The fungicide used was composed by Trifloxystrobin + Prothioconazole (70.0 + 60.0 g active ingredient/ha) with addition of Aureo® at 0.375 L commercial product/ha. The parameters evaluated were: median volume diameter (MVD), covered area (%), drop density (cm2), area under the disease-progress curve (AUDPC), productivity (kg/ha), thousand seed weight, hectoliter weight and the Normalized Difference Vegetation Index (NDVI). The obtained results indicate that the penetration and the area covered by the fungicide volume are higher when high application rates are used alongside fine droplet spectrum. It was found that the fungicide application with fine droplet spectrum and higher spray volumes provides an increase on the control of wheat rust. The fungicide application held at 09:00 presented the best rust control.